Theater and martial arts in West Sumatra : Randai and silek of the Minangkabau - Pauka, Kirstin, 1963- (Monographs in international studies. Southeast Asia series, 1998)
Randai, the popular folk theater tradition of the Minangkabau ethnic group in West Sumatra, has evolved to include influences of martial arts, storytelling, and folk songs. Theater and Martial Arts in West Sumatra describes the origin, development, and cultural background of randai and highlights two recent developments: the emergence of female performers and modern staging techniques. This book also explores the indigenous martial arts form silek, a vital part of randai today. The strong presence of silek is illustrated in the martial focus of the stories that are told through randai, in it.